Johann Friedrich Agricola (1720–1774): a critical study and catalogue of the musical sources - Frampton, AL (2021)
The Berlin Hofkomponist Johann Friedrich Agricola (1720–1774) is today still perhaps best known as a pupil and copyist of Johann Sebastian Bach. Together with Carl Philipp Emanuel Bach, he co-authored Bach’s 1754 obituary, and later received acclaim for his translation and revision of Pier Francesco Tosi’s singing treatise, published in German as 'Anleitung zur Singkunst' (1757). However, Agricola’s own musical legacy has received very little attention, despite the fact that he composed a substantial quantity of music across a range of genres and was also a prolific copyist of works by many major composers of his day. These sources demand attention as both the legacy of an important Berlin composer schooled in the Bach tradition, and, more broadly, as case studies in the rich and complex networks of musical exchange that occurred between composers and musicians during this period.